Strategia polityczna Monarchii Jordańskiej w warunkach zagrożenia jej egzystencji – na przykładzie kryzysów w latach 1957, 1970 i 1991 - Wróblewski, Bartosz (Polityka i Społeczeństwo, 2020)
The Hashemite Kingdom of Jordan is now one of the most stable Arab countries. Several times in its history, however, it underwent area period of serious internal conflicts. Jordan is a monarchy and the authority of the house of Hashemite comprises an axiom of its constitution. In 1957 and 1970 strong opposition dominated by the Palestinians posed a threat to the rule of the Hashemites. In 1991 the throne was not directly in danger, but the results of the Gulf War were destabilizing within the country. The article presents those three political crises and the way in which king Hussein defeated the opposition forces. The Hashemite made use of main internal divisions in Jordanian society, especially the antagonism between Palestinians and the citizens of Transjordan. This strategy has, until now, been effective.